THE CHALLENGES TO DEVELOPING SMART AGRICULTURAL VILLAGE IN THE INDUSTRIAL REVOLUTION 4.0.: THE CASE OF INDONESIA - Tumiwa, Johan Reineer; Tuegeh, Octavia; Bittner, Beata; Nagy, Adrian (Torun International Studies, 2022)
Nowadays, rural depopulation is one of the biggest problems in developed and developing countries, especially due to the COVID-19 pandemic. This pandemic impacts various sectors, especially the economic sector. However, the development of the 4.0 Industrial Revolution forced all sectors, including agriculture, to adapt and take advantage of internet-based digital technology by developing smart agriculture. Therefore, the objective of this study is to analyze the development of smart agriculture in rural areas. This study uses a systematic literature review with a TAA approach with secondary data collected from Scopus databases. The downloaded documents will be further analyzed using VOSviewer software to find the clustering. After the coding process by first-order categories, second layer theme, and aggregate dimension, this research found several theoretical concepts about the “Smart Village”. The definition of the ‘smart village’ concept is a combination of smart agriculture and industry 4.0 technology utilized by rural MSMEs to use the information and communication technology integrated into public services and economic activities. There are still many obstacles encountered in the application of ‘smart villages,’ such as the lack of youth participation and the low quality of human resources in the agricultural sector, limited internet network coverage, and the lack of optimal capital support. This research will contribute to the systematic literature review method by purposing filtering criteria of TAA to shade the light of the lack of data accuracy in several leading databases of scholarly impacts. This research also gives a clear direction for further research regarding industry 4.0 and Indonesia's smart agriculture concept application.